A survey on Malaysian community pharmacists' perceptions of and barriers to mandatory continuous education - Elsayed, Tarek Mohamed Ali; Othman, Noordin (2013)
Continuous Professional Development (CPD) has been made mandatory in Malaysia for pharmacists in private sector effective January, 2012. The aim of this cross-sectional study was to assess the community pharmacists’ knowledge, perceptions of current CPD requirements and their involvement in it. A self-administered anonymous questionnaire was mailed to all community pharmacies in Malaysia. Response rate was 18.6%. An 88.1% of respondents showed knowledge of current CPD requirements. The majority agreed that CPD is essential to keep them updated, the current CPD requirements are adequate to keep them updated, their participation in CPD events will be reflected in their pharmacy practice and that making CPD mandatory motivates them to participate. Only 35.3% agreed that the currently available CPD resources are adequate and 49.7% found that CPD target is achievable. A significantly higher agreement existed among chain pharmacies pharmacists (who are known to have in-house CPD program) compared to those working in independent pharmacies (73.5% and 45.2% respectively, P = 0.001). The most common motivator to attend face-to-face CPD events was the interesting topics, while overlap with work schedule was the most common barrier. One-day CPD event was the most preferred CPD mode and the most attended. Innovations in disease management was the most preferred CPD content area. Mandatory CPD policy resulted in a significant increase in the mean CPD points accumulated by respondents. Conclusion: The majority of community pharmacists showed enthusiasm to CPD and perceived it positively. Many factors should be considered to make it more accessible for them.